2005
DOI: 10.1136/bjsm.2004.016915
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and physiological profiles of sepak takraw players

Abstract: Objectives: Anthropometric and physiological profiles of national sepak takraw players were determined. Methods: Thirty nine players, specialising in the three playing positions (tekong/server, feeder, and killer/ spiker) were divided into three age categories of under 15 (U15), under 18 (U18), and under 23 (U23) years of age. Height, weight, percent body fat (%bf), maximum oxygen consumption (Vo 2max ), range of motion (ROM), back and leg strength, and heart rate, for the estimation of oxygen consumption duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 11 publications
2
24
1
3
Order By: Relevance
“…5162, Japan) according to a protocol [10] which has been validated in both adolescents and adults [10], [11].…”
Section: Methodsmentioning
confidence: 99%
“…5162, Japan) according to a protocol [10] which has been validated in both adolescents and adults [10], [11].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we conclude that hip extension restriction is associated with HSI in sepak takraw. Jawis et al reported that under-23 sepak takraw players had better ROM measurements in all the joints than those found in under-15 and under-18 sepak takraw players on the Malaysian national team [15]. In addition, greater experience induced better ROM and reduced HSI in sepak takraw.…”
Section: Small Hip Extension Rommentioning
confidence: 95%
“…Sepak takraw is a popular sport in Southeast Asia. It is now played worldwide [15]. "Sepak" means to kick in Malay, and "takraw" means ball in Thai.…”
Section: Introduction ▼mentioning
confidence: 99%
See 1 more Smart Citation
“…It is due to the players have to jump up from a hard flooring court and then roll forward or backward to kick the ball in the air, thus they are susceptible of getting various forms of sports injuries [14] . On the other hand, a study on the anthropometric and physiological profiling conducted by Jawis, Singh, Singh, and Yassin [15] showed that three playing positions (tekong/serve, feeder, and killer/spiker) produced different levels of heart rate, oxygen consumption, and VO2max during a match in which the killer group exhibited higher levels physiological changes compared to the tekong and feeder. Thus, more studies should be investigated looking into the psychological and also the physiological aspects of Takraw's risk of injuries among to prevent the players from getting sports injuries.…”
Section: Introductionmentioning
confidence: 99%